Chaos Control and Behavior Analysis of a Discrete-Time Dynamical System with Competitive Effect (Journal of Nonlinear Modeling and Analysis, 2025)
This paper is about a class of discrete-time dynamical systemswith competitive effects. The local stability of the positive equilibrium pointof the system and the conditions for the existence of flip bifurcation andNeimark-Sacker bifurcation are discussed by using the center manifold theoremand bifurcation theory. In addition, the direction of the flip bifurcation andNeimark-Sacker bifurcation is given. Furthermore, a feedback control strategyis employed to control bifurcation and chaos in the system. Finally, flip bifurcation, Neimark-Sacker bifurcation and chaos control strategy are verifiedwith the help of numerical simulations.